Associations among amino acid, lipid, and glucose metabolic profiles in childhood obesity - Yosuke Suzuki; Jun Kido; Shirou Matsumoto; Kie Shimizu; Kimitoshi Nakamura (BMC, 2019)
Abstract Background Plasma-free amino acid profiles have been reported to correlate with obesity and glucose metabolism, and have been studied as potentially useful biomarkers of lifestyle-related diseases affecting metabolism in adulthood. However, knowledge of these relationships is lacking in children, despite the growing public health problem posed by childhood obesity. The aim of this study was to assess whether plasma-free amino acid profiles can serve as useful biomarkers of lifestyle-related diseases in children with obesity. Methods This retrospective study used the medical records of 26 patients (15 male, 11 female) aged 9 or 10 years presenting with moderate to severe obesity and hyperlipidemia between April 2015 and March 2017. A degree of obesity of 30% or more was defined as moderate or severe. Amino acid levels were compared between obese children with and without impaired glucose tolerance using a t-test or Mann-Whitney U test. In addition, the influence of factors such as intima media thickness, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, amino acids, and homeostasis model assessment-insulin resistance (HOMA-IR) were analyzed pairwise using Pearson's correlation or Spearman's rank correlation. Results HOMA-IR was positively correlated with valine, leucine (Leu), isoleucine, phenylalanine, tryptophan, methionine, threonine, lysine, alanine, tyrosine, glutamate (Glu), proline, arginine, ornithine, total free amino acids (all P < 0.01), and aspartate (P = 0.010). Moreover, blood uric acid levels were positively correlated with Leu (P = 0.005) and Glu (P = 0.019), and negatively correlated with serine, glycine, and asparagine (P = 0.007, P = 0.003, and P = 0.013, respectively). Conclusions Amino acid profile reflects impaired glucose tolerance and hyperuricemia at an early stage of obesity. It is therefore a useful marker to inform early intervention in children with obesity, as in adults.